The mediating role of perceived value and social media word-of-mouth in the relationship between perceived quality and purchase intention - Teguh Widodo; Ni Luh Putu Krisma Maylina (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to investigate the effect of perceived quality on purchase intention mediated by the perceived value and social media WOM. The process involved testing the cause-and-effect relationships between the variables used in the structural equation model (SEM) empirically using primary data from an online survey of 410 Garuda Indonesia Airline passengers. The five-scale ordinal data retrieved from the 27 question items presented to the respondents were later processed using LISREL statistical software. The analysis produced several findings, first, the perceived value dimensions were directly affected by the perceived quality and also have a direct influence on social media WOM, second, social media WOM directly affected purchase intention, third, perceived value dimensions played a mediating role between perceived quality and purchase intention, and fourth, social media WOM had a mediating influencing on the effect of perceived quality on purchase intention. This simply means that perceived quality indirectly and significantly affected purchase intention through the mediation of perceived value dimensions and social media WOM.